Modeling the influence of cloudiness on diffuse horizon-tal irradiation under various sky conditions in Nigeria - Nwokolo, Samuel; Ogbulezie, Julie (International Journal of Physical Research, 2017)
In this study, modeling the influence of cloudiness on diffuse horizontal irradiation (DHI) in six tropical ecological zones in Nigeria (Latitude 4.75-13.067oN and Longitude 3.333-13.16oE) using 22-year data (July 1983- June 2005) was analysed for all sky and clear sky conditions. The result revealed that the absorption of DHI in the global horizontal irradiation (GHI) portion of the solar spectrum is greatly enhanced in the Southern tropical zones as a result of heavy presence of smog, cloudiness, and high water vapour parameters such as relative humidity, dew point temperature and precipitable water thereby increasing the diffuse fraction in the zone. However, in the Northern tropical zones, the absorption of DHI in the GHI portion of the solar spectrum lowered due to presence of low smog, cloudiness and low water vapour parameters thereby reducing the diffuse fraction in the region. The quadratic regression correlation model developed deeming from the model performance test indicates that the proposed model could be used to estimate DHI accurately over the six tropical ecological zones in Nigeria and other locations with comparable sky condition to Nigeria.